Validação de método analítico por cromatografia líquida de alta eficiência para doseamento do adapaleno em suspensões de nanocápsulas - Barrios,Jerusa Goi (2011)
Adapalene is a retinoid drug often used for disorders of the skin, mainly acne. In this work, an analytical method for the quantification of adapaleno in suspensions of nanocapsules by HPLC was developed and validated. The method was linear in the range of 10-30 µg mL-1, with a good correlation coefficient (r = 0.994). Precision and accuracy analysis showed low relative standard deviation (< 4.6%) and a good recovery percentual (98.2-106.9%). The procedure was specific, linear, precise, exact and robust so that the method can be applied in quantification of adapalene in suspensions of nanocapsules.